Bifunctional catalyst design for hydrogenation-dehydrogenation cycle of liquid organic hydrogen carrier couples by multi-criteria decision method - Al, Kubra; Tekeli, Fatma Noyan; Filiz, Bilge Coskuner; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Liquid organic hydrogen carriers (LOHCs) are a promising solution for safe and long-distance hydrogen carriers in the hydrogen (H2) value chain relying on the reversible hydrogenation-dehydrogenation cycle. The efficient performance and economic feasibility of this approach are based on the design of efficient and selective bifunctional catalysts for LOHC cycles. This paper provides a systematic bifunctional catalyst design approach for LOHC hydrogenation-dehydrogenation cycles using a multi-criteria decision-making (MCDM) approach. The analytical hierarchy process (AHP) combined with technique for order preference by similarity to ideal solution (TOPSIS) was used to selected the best bifunctional catalyst based on active metal phase, support material, synthesis method steps, and process-related parameters. The catalyst exhibiting the best performance was synthesized via a incipient wetness impregnation method (IWIM), involving drying and reduction steps following the pretreatment stage. Based on this MCDM analysis, the Pd-Ru (2-2 wt%) catalyst supported on Al2O3 emerged as the most active bifunctional catalyst with long term stability, hydrogenation and dehydrogenation steps for LOHC couples. This study demonstrates in embedding MCDM tools into the rational design of bifunctional LOHC catalysts, thereby establishing a quantitative and systematic pathway for pre-experimental catalyst selection. The proposed framework offers a transferable decision-support methodology that can facilitate and accelerate catalyst development in LOHC-based H2 storage and transportation systems.
Keywords: Liquid organic hydrogen carrier; Bifunctional catalyst; Multi-criteria decision method; SUPPORTED CATALYSTS; DRYING CONDITIONS; N-BUTANE; STORAGE; IMPREGNATION; NANOPARTICLES; EFFICIENT; ISOMERIZATION; PERFORMANCE; 2ND-STAGE; Thermodynamics; Energy & Fuels